2010
DOI: 10.1007/s00330-010-1774-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of MR imaging findings differentiating cavernous haemangiomas from schwannomas in the orbit

Abstract: ObjectiveIt is important to distinguish between orbital cavernous haemangioma and schwannoma because the treatments of choice for the two tumours are different. The aim was to evaluate MR imaging findings distinguishing the two tumours.MethodsMagnetic resonance imaging including T1- and T2-weighted imaging and contrast-enhanced MR imaging was performed in 43 patients with cavernous haemangiomas and 16 patients with schwannomas confirmed by pathology. Location, configuration, margins, signal intensity, homogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 19 publications
4
32
1
1
Order By: Relevance
“…The cavernous hemangioma was found in all four quadrants, but among them more cavernous hemangiomas were located in inferolateral quadrant and fewer cavernous hemangiomas were located in superomedial quadrant. Previous studies reported similar result to our study [12][13]. Most of the pleomorphic adenoma, dermoid cyst, lymphoma, adenoid cystic carcinoma and inflammatory pseudotumor, solitary fibrous tumor are located in superolateral quadrant.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The cavernous hemangioma was found in all four quadrants, but among them more cavernous hemangiomas were located in inferolateral quadrant and fewer cavernous hemangiomas were located in superomedial quadrant. Previous studies reported similar result to our study [12][13]. Most of the pleomorphic adenoma, dermoid cyst, lymphoma, adenoid cystic carcinoma and inflammatory pseudotumor, solitary fibrous tumor are located in superolateral quadrant.…”
Section: Discussionsupporting
confidence: 91%
“…Our study showed that mostly cavernous hemangioma were with well-defined margin, oval/ round shaped, intraconal space, slightly high density, low signal intensity on T1WI, high signal intensity on T2WI and gradual homogeneous enhancement (Figure 2). The previous result was similar finding with our result [12,[17][18][19]. Schwannoma is a rare orbital tumor that from Schwann cell in the peripheral nervous system [20][21][22].…”
Section: Orbital Hemangiomasupporting
confidence: 92%
“…Subsequently, contrast enhancement persists in the delayed equilibrium phase, and the enhancing areas increasingly enlarge. 17 Similar enhancement characteristics are shared by cavernous hemangiomas. 18 With regard to the corresponding TIC, an unexpected result was that 70.0% (21/30) of lesions demonstrated the pattern of rapid enhancement and rapid washout (type III) frequently seen in malignancy.…”
Section: Discussionmentioning
confidence: 93%
“…It is a peripheral nerve sheath tumor originating purely from Schwann cells. 19,20 The pathologic feature of schwannoma is characteristic, with the tumor composed of Antoni A and Antoni B patterns in variable proportions. The Antoni A pattern appears solid, while the Antoni B pattern shows loose myxomatous tissue.…”
Section: Discussionmentioning
confidence: 99%
“…12 Although pathologic features of SFT are different from those of schwannoma, orbital SFT and schwannoma show similar clinical findings, making differential diagnosis difficult in clinical practice. 2,3,8,11,19,28 Therefore, a noninvasive method to distinguish SFT from schwannoma in the orbit could be clinically useful, especially in cases in which biopsy would be particularly difficult or the patient is not a good candidate for surgical resection. Many lesions present as round or ovoid masses in the orbit, notably cavernous hemangioma, schwannoma, pleomorphic adenoma of the lacrimal gland, dermoid cyst, and SFT of the orbit.…”
Section: Discussionmentioning
confidence: 99%